Clay mineral transformation mechanism modelling of shale reservoir in Da’anzhai Member, Sichuan Basin, Southern China - Yang, Leilei; Lu, Longfei; Li, Xiaowei; Shan, Yansheng; Mo, Chenchen; Sun, Meng; Hu, Jing; Liu, Weibin; Liang, Baoxing; Xu, Jin (Frontiers in Earth Science, 2023)
Shale reservoirs often undergo intense clay mineral transformation, which plays a crucial role in the formation and evolution of pores. The reservoir lithofacies types of Da'anzhai Member in the Sichuan Basin are complex, the heterogeneity is strong, and the transformation mechanism of clay minerals is unclear, limiting the understanding of reservoir diagenesis and reservoir formation mechanism. In this study, we selected the typical shale reservoir in the Da'anzhai Member of the eastern Sichuan Basin and innovatively introduced the multiphase fluid-chemical-thermal multi-field coupled numerical simulation technique to focus on the dissolution, precipitation and transformation laws of diagenetic minerals in the shale reservoir. We calculated the transformation of diagenetic minerals and their physical response under different temperatures, pressure and fluid conditions and identified the main controlling factors of mineral transformation in shale reservoirs in the study area. The results show that the transformation of smectite to illite in the Da'anzhai Member is a complex physicochemical process influenced by various factors such as temperature, pressure, fluid, and lithology. The increase in temperature can promote illitization until the critical temperature of 110-115°C, below which the conversion rate of smectite to illite increases as the temperature increases. However, when it is higher than the critical temperature, the degree of illitization decreases. In specific K-rich fluids, organic acids significantly affect the conversion of clay minerals in the Da'anzhai Member of the formation. The acidic fluid promotes the dissolution of minerals such as Kfeldspar and releases K + , thus provides the material basis for illitization. The research results provide theoretical support for the diagenetic and formation mechanism of the shale reservoir in the